2017
DOI: 10.18869/nirp.ijpcp.23.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Spouse Abuse and Depressive Symptoms in Women: The Moderating Role of Personality Characteristics

Abstract: Objectives Spouse abuse against women is the most prevalent type of family violence, and its harmful consequences threaten both women's health and their well-being in family and society. It is very important to find the factors that eliminate these deleterious effects and protect women's health. The aim of this study was to explore the moderator effect of personality characteristics in the relationship between spouse abuse and symptoms of depression among women. Methods For this purpose, 300 married women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…In this scale, scores 0 to 13 indicate lack of depression, 14 to 28 indicate low depression, 29 to 44 indicate medium depression, and 45 to 62 indicate severe depression. 27 Respondents with low depression scores were included in the present study, and participants with medium and severe depression scores were referred to psychiatric care. The reliability and validity of this scale were measured in 1971, 1979, 1986, and 1986.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this scale, scores 0 to 13 indicate lack of depression, 14 to 28 indicate low depression, 29 to 44 indicate medium depression, and 45 to 62 indicate severe depression. 27 Respondents with low depression scores were included in the present study, and participants with medium and severe depression scores were referred to psychiatric care. The reliability and validity of this scale were measured in 1971, 1979, 1986, and 1986.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with low-to-medium anxiety were included in the study, and those with severe anxiety were excluded. 26 27 28 29 30…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iranian studies have also shown that women who have experienced any form of IPV might suffer from mental health problems such as depression (Dasarband et al, 2017) and PTSD (Rashti and Golshokouh, 2010) that needed further treatment and psychological rehabilitation. Feelings of low self-worth (Shoakazemi, 2016) and dehumanization (Shahbazi et al, 2018), psychosomatic complaints, sexual problems, increased tendency to use/abuse drugs and alcohol, divorce, and infidelity (Noori et al, 2016) were some other consequences of IPV uncovered in Iranian studies.…”
Section: Intimate Partner Violence In Iranmentioning
confidence: 99%